Ripple formation in weakly turbulent flow - Wierschem, Andreas; Groh, Christopher; Rehberg, Ingo; Aksel, Nuri; Kruelle, Christof A. (European Physical Journal E, 2008)
The formation of granular ripples under liquid shear flow in an annular channel is studied experimentally. The erodible granular bed is subject to weakly turbulent flows without a defined sharp boundary layer close to the granular bed. The flow field and the degree of turbulence is characterized quantitatively by using a particle image velocimeter and a laser-Doppler velocimeter, respectively. A new range of particle Reynolds numbers at the lower limit of the Shields diagram were explored. Quantitative measurements of the granular flow on the surface reveal that the threshold for particle motion coincides within the order of one percent with the threshold for ripple formation. In fully developed ripples it was found that on the leeward side of the ripples regions of low-velocity gradients exist where granular motion is scarce, indicating that the coupling between the ripples is mainly caused by the flow field of the liquid. © 2008 EDP Sciences, Società Italiana di Fisica and Springer-Verlag.
UnivIS-Import:2015-03-09:Pub.2008.tech.ITC.stmmec.ripple